2016
DOI: 10.1016/j.specom.2016.03.002
|View full text |Cite
|
Sign up to set email alerts
|

An acoustic investigation of the developmental trajectory of lexical stress contrastivity in Italian

Abstract: We examined whether typically developing Italian children exhibit adult-like stress contrastivity for word productions elicited via a picture naming task (n=25 children aged 3–5 years and 27 adults). Stimuli were 10 trisyllabic Italian words; half began with a weak–strong (WS) pattern of lexical stress across the initial 2 syllables, as in patata, while the other half began with a strong–weak (SW) pattern, as in gomito. Word productions that were identified as correct via perceptual judgement were analysed aco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 60 publications
1
17
0
Order By: Relevance
“…The findings we report here have implications for research relying only on perceptual judgements of speech production. Like the earlier studies by Ballard et al (2012), Arciuli and Ballard (2017), and Arciuli and Colombo (2016), our findings suggest that, even when word productions are correct via perceptual judgements, there can be fine-grained acoustic differences in the way stress contrastivity is realised. In addition, our findings suggest that these subtle acoustic differences may interact with the stress pattern of target words.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The findings we report here have implications for research relying only on perceptual judgements of speech production. Like the earlier studies by Ballard et al (2012), Arciuli and Ballard (2017), and Arciuli and Colombo (2016), our findings suggest that, even when word productions are correct via perceptual judgements, there can be fine-grained acoustic differences in the way stress contrastivity is realised. In addition, our findings suggest that these subtle acoustic differences may interact with the stress pattern of target words.…”
Section: Discussionsupporting
confidence: 79%
“…In the current study we explored stress contrastivity in children with ASD versus typically developing (TD) children group-wise matched on age and vocabulary. We used the same methodology reported in recent studies of TD individuals that analysed stress contrastivity acoustically (Arciuli & Ballard, 2017;Arciuli & Colombo, 2016;Ballard, Djaja, Arciuli, James, & van Doorn, 2012).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Stimuli were natural syllables, but the same syllable was repeated three times across the string, thus producing a stimulus that is neutral at both the semantic and the lexical levels of analysis. Thus we may hypothesize that the reason why previous authors found that duration, and not pitch, was the critical feature in stress perception, is that some interaction occurs between the lexical/semantic levels and the early acoustic analyses in this process (Arciuli and Colombo, 2016), which changes the relative weight of the parameters in determining performance. Note that even in studies using pseudowords there might have been an implicit lexical contribution, as pseudowords partially activate the phonological lexicon and do so as a function of orthographic/phonological similarity (Rosson, 1983) (e.g., the pseudoword /tavoga/ is very likely to activate the lexical node /tavola/, table).…”
Section: Discussionmentioning
confidence: 93%
“…The pairwise variability index (PVI) was originally conceptualized as the normalized duration difference between adjacent syllables in connected speech and used to characterize speech rhythm and stress in neurotypical speakers who use different languages and dialects (Low, Grabe, & Nolan, 2000). Direct application to running speech has been possible for communication disorders that do not primarily affect linguistic fluency (Knight & Cocks, 2007; Maruthy, Venugopal, & Parakh, 2017) and, when modified for comparisons at the word level, the PVI has contributed to research addressing lexical stress development in children (Arciuli & Ballard, 2017; Arciuli & Colombo, 2016; Ballard, Djaja, Arciuli, James, & van Doorn, 2012) and the differentiation between AOS and aphasia (APH).…”
Section: Ratios For Lexical Stressmentioning
confidence: 99%